ANALYSIS OF TEACHER ABILITY IN USING LEARNING TECHNOLOGY: SYSTEMATIC LITERATURE REVIEW (SLR) - Agung Indrianingsi; Hotmaulina Sihotang; Bintang Simbolon (RADJA PUBLIKA, 2025)
This study aims to synthesize findings from the latest scientific literature related to teachers' ability to integrate learning technology. A Systematic Literature Review (SLR) approach was used to examine 20 articles published between 2019 and 2024, focusing on factors influencing teachers' technological competence. The review results indicate that teachers' competence is influenced by four main aspects: (1) ongoing professional training, (2) availability of infrastructure and institutional support, (3) teachers' self-efficacy, and (4) digital attitudes and literacy. Despite the increasing adoption of technology, challenges remain in teachers' pedagogical ability to integrate technology effectively. This study recommends improving training based on the TPACK model and strengthening school policies to support digital transformation in education.